(untitled) (International Journal of Communication Systems and Network Technologies, 2013)
The system proposed in this paper is for monitoring the speed and torque in induction motors in real time by employing ZigBee based wireless sensor network. The electrical signals from the motors are acquired in a noninvasive manner. An IR sensor is used here. The processing for speed and torque estimation is done locally by the embedded system. Speed of the motor can be controlled by the embedded system. The values calculated by the embedded system are transmitted to a monitoring unit through ZigBee based wireless sensor network. Monitoring of various induction motors can be done at the base unit. Speed of deployment, maintenance, low cost, low power consumption and reliability are the main advantages of using ZigBee.